Cultural Harmony: East Loloan Traditional Marriage in Jembrana Regency (A Comparative Study of Islamic Law and Customary Law) - Rizal Fahmi (QURU’: Journal of Family Law and Culture, 2024)
One of the religious recommendations to improve the lives of its people is through the institution of marriage. Marriage plays an important role in human life. In the East Loloan community, a common phenomenon is the very important preparation and implementation of the kelakat ritual for the bride and groom before marriage. Failure to perform or breaking this tradition is often associated with unwanted events such as trance, chronic illness, or undercooked dishes. Therefore, the families of the bride and groom are very careful in carrying out the wedding ceremony in order to avoid bad luck. The subject matter debated in this thesis is the perspective of Islamic law and customary law on the tradition of the wedding procession in East Loloan. This research is a field study with a qualitative approach. Data were obtained through interviews, observations, and documentation studies. The research approach is descriptive-comparative with a normative approach. The conclusion of this study is that although the kelakat tradition is considered valid according to custom and is passed down from generation to generation by the local community, this approach is different in principle from Islamic teachings. However, in practice in East Loloan, there are efforts to achieve similar goals between customary marriage and Islamic law, namely maintaining harmony and justice in marital relationships.